PUTUSAN KONSTITUSIONAL DEMOKRATIS TERHADAP SENGKETA PEMILU SERENTAK MENURUT FIQIH SIYASAH - Wira Purwadi; Edi Gunawan; Devi Restiani Susilo; Johana Manuhuwa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2022)
The Constitutional Court is a judicial institution that has the authority to resolve disputes over general election results. The purpose of this study is to analyze the challenges of the Constitutional Court in producing democratic constitutional decisions on 2024 simultaneous election disputes and to analyze its authority in producing democratic constitutional decisions on 2024 simultaneous election disputes from the perspective of Islamic constitutional law (fiqh siyasah). This type of research is a combination of normative research and empirical law. The results of the research show that the Constitutional Court faces several challenges in the 2024 Simultaneous Elections, namely: readiness to provide optimal service, intense political pressure for the presidential election, time issues and quality of decisions. The decision of the Constitutional Court must truly reflect a fair and just decision within the framework of implementing constitutional democracy. In the perspective of fiqh siyasah, the decisions of the judges of the Constitutional Court must provide a sense of justice for the people, and this is implemented if the constitutional judges have statesmanship, prioritize substantive justice, not become mouthpieces for the law, so that the decisions of the Constitutional Court must uphold constitutional democratic values based on justice. in the name of God Almighty.